The Influence of the Problem Based Learning Model Assisted by Media Bio Briquettes to Students ' Science Process Skills - Desti Shinta Kurniawati; Suryawan, Ari; Rahmawati, Puji (Journal of Elementary School Education, 2023)
Moment This Still there are teachers who do activity science learning only limited convey concept. Should more science learning emphasis on process skills, consequently student only just learn material without own process skills, so science process skills student Still less. Use of Problem Based Learning models assisted by bio- briquette media is one possible solution done For solve problem the. Research This aim For now the influence of the Problem Based Learning model assisted by bio- briquette media to science process skills student class IV SD Negeri Borobudur 1. Method research used in study This that is experiment with use design pre-experimental one group pretest-posttest. The sample used in study This as many as 20 students class IV A Borobudur State Elementary School 1. The sampling technique used is purposive sampling. Instruments used in study This that is pretest-posttest and sheets observation student. Results obtained in study This show that there is the influence of the Problem Based Learning model assisted by bio- briquette media to science process skills student. it proven that the average result of the pretest value is 40.43 < posttest 79.53. Next, test the paired sample t-test obtain results significance (2 tailed ) 0.000<0.05, so can concluded that the Problem Based Learning model assisted by bio- briquette media influential significant to science process skills student.